2018
DOI: 10.1016/j.joms.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The CCL5/CCR5 Chemotactic Pathway Promotes Perineural Invasion in Salivary Adenoid Cystic Carcinoma

Abstract: Our results suggest a pivotal role of CCL5/CCR5 axis in tumor-nerve interactions during PNI of SACC. The CCL5/CCR5 pathway might prove to be an attractive new target for the treatment of SACC with PNI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Herein, we detected immunoreactivities for both CCL3 and CCR5 in the tumor nests of human ESCC tissues. These observations are consistent with those of immunohistochemical and immunofluorescent examinations of CCL3 and CCR5 in human or murine cancer tissues [ 17 , 20 , 21 , 23 , 26 , 27 , 32 , 34 36 ]. Our examination of double IF showed that CCL3 was expressed in both neoplastic cells and TAMs in the tumor nest of human ESCC tissue.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Herein, we detected immunoreactivities for both CCL3 and CCR5 in the tumor nests of human ESCC tissues. These observations are consistent with those of immunohistochemical and immunofluorescent examinations of CCL3 and CCR5 in human or murine cancer tissues [ 17 , 20 , 21 , 23 , 26 , 27 , 32 , 34 36 ]. Our examination of double IF showed that CCL3 was expressed in both neoplastic cells and TAMs in the tumor nest of human ESCC tissue.…”
Section: Discussionsupporting
confidence: 89%
“…A high plasma level of CCL3 was associated with poor survival rate in chronic lymphocytic leukemia [ 66 ] and diffuse-large B-cell lymphoma [ 67 ]. CCR5 was reported to be associated with poor overall survival in breast cancer [ 34 ], poor relapse-free survival in prostate cancer [ 68 ], high histological grade in pancreatic cancer [ 35 ], and perineural invasion in salivary adenoid cystic carcinoma [ 36 ]. The present study is the first report which revealed that the expression of both CCL3 and CCR5 in human cancer tissue is associated with poor patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNI was defined as described previously 6. The IHC assay was performed using the streptavidin–biotin–peroxidase method, as we have previously described 13. Briefly, 5-μm-thick sections were cut from formalin-fixed, paraffin-embedded tissue specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with the development of tumor microenvironment theory, an increasing number of studies have focused on reciprocal interactions between tumor cells and nerves 11. For example, we have investigated the effects of nerve growth factor and chemokine (C-C motif) ligand 5/C-C chemokine receptor type 5 signaling on PNI in SACC 13. In addition, data from several recent studies indicated that the sympathetic nervous system may play a key role in tumor progression 14,15.…”
Section: Introductionmentioning
confidence: 99%